Speculative Investor Behavior in a Stock Market with Heterogeneous Expectations - Harrison, J. Michael; Kreps, David M. (Quarterly Journal of Economics, 1978)
I. Introduction, 323.—II. Formulation, 325.—III. An example, 326.—IV. Consistent price schemes, 328.—V. Back to the example, 332.—VI. Relaxing the assumptions, 333.—VII. Concluding remarks, 334.